Implementation of an Integrated Lung Cancer Prevention and Screening Program Using a Mobile Computed Tomography (CT) Unit in Brazil - Rodrigo Sampaio Chiarantano; Fabiana Lima Vazquez; Alexander Franco; Larissa Cristina Ferreira; Maraísa Cristina da Costa; Thais Talarico; Ângela Neves Oliveira; José Elias Miziara; Edmundo Carvalho Mauad; Eduardo Caetano da Silva; Luis Marcelo Ventura; Raphael Haikel Junior; et al. (Cancer Control, 2022)
Introduction Lung cancer is the deadliest cancer worldwide and in Brazil. Despite strong evidence, lung cancer screening by low-dose computed tomography (LDCT) in high-risk individuals is far from a reality in many countries, particularly in Brazil. Brazil has a universal public health system marked with important inequalities. One affordable strategy to increase the coverage of resources is to use mobile units. Objectives To describe the implementation and results of an innovative lung cancer prevention program that integrates tobacco cessation and lung cancer screening using a mobile CT unit. Methodology From May 2019 to Dec 2020, health professionals from 18 public primary health care units in Barretos, Brazil, were trained to offer smoking cessation counseling and treatment. Eligible high-risk participants of this program were also invited to perform lung cancer screening in a mobile LDCT unit that was specially conceived to be dispatched to the community. A detailed epidemiological questionnaire was administered to the LDCT participants. Results Among the 233 screened participants, the majority were women (54.9%), and the average age was 62 years old. A total of 52.8% of participants showed high or very high nicotine dependence. After 1 year, 27.8% of participants who were involved in smoking cessation groups had quit smoking. The first LDCT round revealed that the majority of participants (83.7%) exhibited lung-Rads 1 or 2; 7.3% exhibited lung-Rads 3; 7.7% exhibited lung-Rads 4a; and 3% exhibited lung-Rads 4b or 4x. The three participants with lung-Rads 4b were further confirmed, and their surgery led to the diagnosis of early-stage cancer (1 case of adenocarcinoma and two cases of squamous cell carcinoma), leading to a cancer diagnosis rate of 12.8/1000. Conclusion Our results indicate promising outcomes for an onsite integrative program enrolling high-risk individuals in a middle-income country. Evidence barriers and challenges remain to be overcome.